Folk music in the repertoire of the amateur student choir - Kosiborod, Olga (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
This paper examines the problem of student band repertoire policy and the use of folk songs the concert - performing practice is. The goal is to consider some theoretical aspects related to the folklore and folklorisation of choral academic singing and practice of implementing it in the field of amateur choral performances. The oretical studies of domestic scientists and practical work of the author were used as a methodological basis for the article. Folk song was, is and will be a critical component of the musical culture and it is, naturally, presented in the repertoire of the student collective works of this genre and is the most important component for the implementation of all socio - cultural functions inherent in the amateur team.